MBA education at Debrecen University Faculty of Agricultural Economics and Rural Development - Nábrádi, András; Kárpáti , László; Lazányi, János (Applied Studies in Agribusiness and Commerce, 2007)
Debrecen is the capital of the Great Hungarian Plain, the centre of many institutions, organizations and business companies just in the heart of Europe. It has provided an ideal setting for higher education since 1538. With this past of more than 450 years, the University of Debrecen is the oldest higher educational institution in continuous operation in Hungary based in the same city. Higher education in agriculture began in 1868, when the National Higher School of Agriculture was formed in Debrecen. The University of Debrecen has more than 26 000 students, and more than 1700 instructors teach at the University, which has 13 faculties, 2 independent institutions, 20 doctoral schools and offers the widest choice of higher education. This outstanding intellectual centre, with a vast research and development capacity, has a growing importance in the economic and social development, cultural progress of the region. It devotes special attention to serving the needs of a knowledge based society more efficiently, and it strives to become the knowledge centre of the region, which also preserves traditions and values.